Peran Customer Review dalam Meningkatkan Kepercayaan Konsumen pada Filan Official Store di Marketplace Shopee - Nulthazam Sarah; Nur Fadilah Ayu Sandira; Indri Iswardhani; Sri Astuti Nasir; A. Reski Almaida Dg Macenning (Forum Kerjasama Pendidikan Tinggi, 2025)
The development of e-commerce marketplaces has transformed the retail trade landscape, where customer reviews have become vital instruments in building consumer trust in digital environments filled with uncertainty. This study aims to analyze the influence of customer reviews on consumer trust formation at Filan Official Store in Shopee marketplace and identify the most effective key factors. A descriptive quantitative method was employed with a sample of 150 respondents selected through purposive sampling, using structured questionnaires and Pearson correlation analysis to measure inter-variable relationships. Results demonstrate a significant positive relationship between customer reviews and consumer trust with a correlation coefficient of 0.743 (p < 0.01). Review content quality emerged as the dominant factor (28.4%) in building trust, followed by rating consistency (24.7%), reviewer credibility (21.9%), review volume (18.3%), and temporal factors (6.7%). Customer reviews contributed highest to credibility aspects (0.768), benevolence (0.721), and integrity (0.695). The study concludes that customer reviews play a significant role in digital trust ecosystems, with recommendations for implementing strict verification systems, multimedia features, and review curation algorithms for sustainable optimization. Keywords: ,, e-commerce, Shopee marketplace,